Latinx Adolescents' Reading Motivation Profiles and Associations with Higher Education Aspirations. Issue 3 (2nd July 2020) - Quirk, Matthew; Swami, Sruthi; Loera, Gustavo; Garcia, Sergio
ABSTRACT: Reading motivation may help explain some discrepancies in higher education attainment among Latinx adolescents. Using a person-centered approach to understand underlying reading motivation profiles among N = 254 Latinx adolescents, results identified four ordered classes of reading motivation including, (a) a "High" class characterized by high motivation across dimensions, (b) a "High-Practical" class characterized by moderate to high levels of motivation with particular emphasis on practical reasons for reading, (c) an "Apathetic" class with moderate to low motivation across dimensions, and (d) a "Low" class who consistently endorsed low levels of motivation across dimensions. Results also showed reading motivation class membership was significantly associated with demographic covariates (e.g., gender and parent education) and higher education aspirations, consistent with previous research. Practical implications are also discussed.